One Hundred Twenty-One Resected Solid Pseudopapillary Tumors of the Pancreas: An 8-Year Single-Institution Experience at Zhongshan Hospital, Shanghai, China - Xu, Yadong; Zhao, Guochao; Pu, Ning; Nuerxiati, Abulimiti; Ji, Yuan; Zhang, Lei; Rong, Yefei; Lou, Wenhui; Wang, Dansong; Kuang, Tiantao; Xu, Xuefeng; Wu, Wenchuan (Pancreas, 2017)
The aims of this study were to introduce our experience with treating patients with pancreatic solid pseudopapillary tumors (SPTs) and to investigate the clinical risk factors for recurrence of SPTs because no consensus has been established to date. One hundred twenty-one patients underwent surgical resection from January 2008 to December 2015 in our institution. Clinical data were collected from the standardized reports. Of the 121 patients, 93 (76.9%) were women, 28 (23.1%) were men, and the mean age at diagnosis was 33.7 years (range, 11-68 years). Sixty patients were subjected to short-term complications, and 8 patients experienced long-term complications, some of whom may require surgery. The tumor located in the distal pancreas (P = 0.02), and a Ki-67 index value > 1.5 (P = 0.01) indicated malignancy according to the World Health Organization 2000 classification. One hundred three patients responded to follow-up, and 3 cases (2.9%) were subject to liver metastases. Recurrence was more frequently observed in tumors classified as high-grade malignancies according to the World Health Organization 2010 classification (P = 0.013), synchronous metastases (P < 0.001), peripancreatic fat infiltration (P = 0.018), and lymphovascular invasion (P < 0.001). Evaluating the risk of the recurrence of SPTs still requires systematic and multicenter trials in the future, even some pathological features showed statistical differences.